2021
DOI: 10.15639/teflinjournal.v32i1/1-28
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on Willingness to Communicate in English in the Iranian Tertiary Educational Context

Abstract: Willingness to communicate (WTC) in English is specifically important because L2 (foreign/second language) communication is considered to be a key factor in L2 learning. When the opportunity to speak English arises, there are generally two options: speaking or avoiding it. Several factors might exert influence on the choice of either option by different individuals. In this vein, the current study investigated the underlying factors that lead to (un)willingness on the part of Iranian EFL (English as a Foreign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
4
4
0
Order By: Relevance
“…It is consistent with a finding confirming that self-perception of English ability positively correlates to English proficiency and class performance (Dewaele & Furnham, 2008;Takahashi, 2009). Likewise, the finding of this research confirms the one by (Alimorad et al, 2021;Aslan & Şahin, 2020), confirming that one of the factors affecting classroom participation is negative L2 perception and L2 speaking anxiety.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It is consistent with a finding confirming that self-perception of English ability positively correlates to English proficiency and class performance (Dewaele & Furnham, 2008;Takahashi, 2009). Likewise, the finding of this research confirms the one by (Alimorad et al, 2021;Aslan & Şahin, 2020), confirming that one of the factors affecting classroom participation is negative L2 perception and L2 speaking anxiety.…”
Section: Discussionsupporting
confidence: 83%
“…With purposive random sampling, this research recruited ten students and used the semi-structured interview as the method of data collection. Results of the research revealed that WTC arises as the result of interactions involving some factors: individual, contextual, and linguistic factors (Alimorad et al, 2021).…”
mentioning
confidence: 99%
“…By and large, some findings were consistent with the concept of individual factors (Peng, 2019;Alimorad and Farahmand, 2021;Ma et al, 2022) or within-person variability (Zhang et al, 2019), such as themes 3, 6, 11, and 13, and most of the rest are in line with the contextual/environmental factors (Peng, 2019;Alimorad and Farahmand, 2021;Ma et al, 2022) and betweenperson variability (Zhang et al, 2019;. While the previous studies mainly focused on in-class factors that influenced students' L2 WTC, the current study discovered some additional out-of-class factors, like themes 5, 12, and 13, which show students' initiative to use English in real-life situations, and to some extent confirm previous researchers' finding that WTC is socio-culturally constructed as a function of the interaction of individual and environmental factors both inside and beyond the classroom walls (Peng, 2019;Alimorad and Farahmand, 2021;Ma et al, 2022).…”
Section: Similarities Between the Findings Of This Study And Previous...supporting
confidence: 76%
“…The complex, dynamic interaction among individual, contextual, linguistic and educational factors may facilitate or impede L2 WTC of Iranian EFL tertiary students (Alimorad and Farahmand, 2021) and Chinese postgraduate students (Ma et al, 2022). More research is needed to uncover the difference between WTC in using English for general purposes and WTC in EMI settings (Ma et al, 2022).…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation